Ontologi, begreppssystem och WordNet - Ruppel, Klaas (LexicoNordica, 2011)
In this article I try to point out similarities and differences between ontologies, dictionaries of synonyms and word nets. The focus lies on ontologies in relation to the other two types. The universal applicability and language-independentness claimed for top hierarchies of ontologies is also discussed. As examples I look at two ontologies (Suggested Upper Merged Ontology and EuroWordNet Top Ontology), a dictionary of synonyms (Lagercrantz 1939) and the Princeton WordNet and some of its offsprings (EuroWordNet, DanNet). I emphasize particularly the content and the weight of ontological work and do not discuss datatechnology.